TIDAL OCCURRENCE OF PENAEID PRAWN SEED IN THE KALI ESTUARY, KARWAR - Gunaga, Vishnudas; Neelakantan, K; Neelakantan, B (Indian Journal of Fisheries, 2011)
A detailed study was undertaken in the Kali estuary to find out the effect of tidal heights on the penaeidprawn seed abundance. From the study it is indicated that late postlarval and early juvenile stages canbe collected in large numbers for stocking purposes at or near the time of low tide.